Multi-period temporary depot location problem in flood natural disaster response - Wapee Manopiniwes (2019)
© IEOM Society International. Because the formation or reformation of emergency logistics is a complex undertaking, this study proposes a multi-period location-routing model in the immediate aftermath of a flood natural disaster. The model can decide the temporary depot locations and make vehicle routing plans in which the amount of each relief supplies to be transported can be optimally determined. The temporary depot considered in this problem is a facility different from a typical warehouse on the fact that temporary depots are not set up to provide storage, but are created instead to facilitate transferring relief supplies from one carrier type to another carrier type at the flood boundary. The most common transport means used in the real flood problem, trucks and boats, are considered in the model formulation. We begin by explaining the proposed mixed-integer programming model which employs a dynamic approach to locate the temporary depots, after which we conduct a set of numerical experiments to test the model formulation and analyze the characteristics of the optimization problem. The experimental results indicate that, based on flood disaster characteristics, our model is capable of showing the optimal locations of temporary depots in the flood response operations.